Guideline for Minimizing Radiation Exposure of Interventionalists during Fluoroscopy-guided Interventional Procedures - Il Sang Shin; Yun Nah Lee; Jun Kyu Lee; Joo Seong Kim; Sung Bum Kim; Jiyoung Keum; Chang Hoon Oh; Kang Won Lee; Joowon Chung; Lyo Min Kwon; Nam Hee Kim; Sang Soo Lee; et al. (The Korean Journal of Gastroenterology)
As fluoroscopy-guided interventional procedures gain popularity, the associated health threats from radiation exposure to interventionalists during these procedures are increasing. Therefore, an understanding of the potential risks of radiation and careful consideration on minimizing exposure to radiation during the procedures are of paramount importance. The Korean Pancreatobiliary Association has developed a clinical practice guideline to minimize radiation exposure during fluoroscopy-guided interventional procedures. This guideline provides recommendations to deal with the risk of radiation exposure to interventionalists who perform fluoroscopy-guided procedures, and emphasizes the importance of proper and practical approaches to avoid unnecessary radiation exposure.